Predictors of antipsychotic monotherapy with olanzapine during a 1-year naturalistic study of schizophrenia patients in Japan - Ye W; Ascher-Svanum H; Flynn JA; Tanji Y; Takahashi M (Dove Medical Press, 2012)
Wenyu Ye1, Haya Ascher-Svanum2, Jennifer A Flynn3, Yuka Tanji3, Michihiro Takahashi3,41Lilly Suzhou Pharmaceutical Co, Shanghai, People's Republic of China; 2Eli Lilly and Company, Indianapolis, IN, USA; 3Lilly Research Laboratories Japan, Eli Lilly Japan K.K., Kobe, 4Terauchi-Takahashi Psychiatric Clinic, Ashiya, JapanPurpose: Although expert guidelines for the treatment of schizophrenia recommend antipsychotic monotherapy, the use of antipsychotic polypharmacy is common. This study identified characteristics that differentiate patients with schizophrenia who are treated with olanzapine monotherapy versus polypharmacy in usual care in Japan.Patients and methods: In a large (N = 1850) prospective, observational study, Japanese patients with schizophrenia who initiated treatment with olanzapine were followed for 1 year. Consistent with past research, antipsychotic polypharmacy was defined as the concurrent use of olanzapine and another antipsychotic for at least 60 days. Switching was defined as discontinuing a prior antipsychotic therapy rather than augmenting the medication regimen. Predictors of antipsychotic monotherapy were based on information available at the time of olanzapine initiation. Baseline characteristics were compared using t-tests and Χ2 tests. Stepwise logistic regression was used to identify independent predictors of monotherapy.Results: Patients treated with olanzapine monotherapy (43.2%) differed from those treated with antipsychotic polypharmacy (56.8%) on demographics, treatment history, baseline symptom levels, functional levels, and treatment-emergent adverse events. Stepwise logistic regression identified multiple variables that significantly predicted monotherapy: older age, shorter duration of schizophrenia, outpatient status, comorbid medical conditions, lower body mass index, no prior anticholinergic use, no prior mood stabilizer use, and switching from a previous antipsychotic (typical or atypical).Conclusion: Consistent with prior research in Japan, antipsychotic polypharmacy appears to be common in the treatment of schizophrenia. Patients treated with monotherapy could be differentiated from those treated with antipsychotic polypharmacy based on a specific set of demographic and baseline clinical characteristics.Keywords: olanzapine, schizophrenia, polypharmacy, quality improvement